PENERAPAN MODEL-MODEL PEMBELAJARAN SEJARAH MELALUI KEGIATAN SUPERVISI AKADEMIK DENGAN PENDEKATAN REALISTIK DI SMA NEGERI 2 LUBUK BASUNG - Nusir, Ali (STKIP Pesisir Selatan, 2017)
Based on the observations that researchers have done in SMAN 2 Lubuk Basung, it was found that teachers' ability in applying historical learning model is still low. The purpose of this study is to improve the application of historical learning model Through academic supervision with realistic approach in SMAN 2 Lubuk Basung. This study is a school action research. The research procedures in this study include planning, action, obeservation and reflection. This study consists of two cycles with four meetings. Research subjects consisted of 6 teachers of SMAN 2 Lubuk Basung. Research data was collected using obeservation sheets. Data were analyzed using percentages. The results showed that the application of historical learning models through academic supervision with realistic approach can improve the quality of student learning in SMAN 2 Lubuk Basung. This is evidenced by the application of historical learning models through academic supervision with realistic approach can improve the quality of student learning in SMAN 2 Lubuk Basung from cycle I to cycle II. The average ability of students and teachers to make learning models in cycle I is 48 with less category and in cycle II is 82.66 with good category.